PENGARUH METODE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SOAL CERITA MATERI VOLUME BALOK SISWA KELAS V MI AN-NASHRIYAH LASEM REMBANG - Noprastiyaning Ismu Salamah; Zainal Arifin (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
This research is motivated by students difficulties in understanding and solving problems related to story-shape questions in mathematic. The principal issues are analyzed in this study are: to determine influence problem solving method towards on the ability to understand the concept of the story of the fifth grade students of MI An-Nashriyah Lasem, Rembang. The research is experimental elaborated control group pretest posttest design. The study was conducted on 62 students using test, observation and documentation instruments. Based on the results of independent samples t-test showed the influence of problem solving methods on the ability to understand the concept of story problems with a significance level of 0.05> 0.000 indicating an influence. Keywords: problem solving method, concept of story, box volume